Needs Analysis for Maze Game Learning Media to Support Grade 1 Students’ Understanding of Number Concepts - Hety Nurendang; Mardiyana Mardiyana; Supianto Supianto (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the initial needs in the development of Maze Game learning media as a means of improving understanding of the concept of integers in grade 1 elementary school students. The background of this research departs from the problem of students' low understanding of integers due to the use of conventional learning methods and the lack of interactive media that is in accordance with the characteristics of early childhood. This study uses a qualitative descriptive approach with a need analysis method as the initial stage of media development. Data was collected through observation, 2 teacher interviews, and the distribution of questionnaires to 60 student grade 1 in Cluster 03 East Telukjambe District, Karawang Regency. The results of the study showed that learning integers is still centered on teachers with limited media use, students have difficulty recognizing symbols and number sequences, understanding place values, and connecting numbers with the number of objects. Teachers and students need learning media that is engaging, interactive, and easy to use. Maze Game is considered a relevant alternative media because it is able to combine elements of games, challenges, and meaningful learning according to the child's cognitive development stage. Based on the results of this needs analysis, it can be concluded that the development of Maze Game media is very necessary to improve understanding of the concept of integers through a learning while playing approach. The results of this research are expected to be the basis for the product development stage in the next research to produce valid, practical, and effective learning media for elementary school students.